PENGARUH LINGKUNGAN KERJA, NILAI-NILAI SOSIAL, PERTIMBANGAN PASAR KERJA, REGULASI, SERTA KECERDASAN ADVERSITY TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK BERKARIR SEBAGAI AKUNTAN PUBLIK (Studi Pada Mahasiswa PTN di Riau dan Sumatera Barat) - Assiddiqi Assiddiqi; Andreas Andreas; Ilham Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine the effect of the work environment, social values, labor market considerations, regulations, and adversity intelligence on the interest of accounting students for a career as a public accountant (studies at publik universities in Riau and West Sumatra). The sample is determined using the Slovin formula. So that it obtained 256 samples of students majoring in Accounting who became respondents. This study used primary data obtained from respondents' answers and distributed questionnaires. The collected data were analyzed using data analysis methods by first proposing classical assumptions before conducting hypothesis testing. Classic assumption tests and hypothesis testing were carried out using SPSS version 16.0 software. The results of this study concluded that the Work Environment, Social Values, and Adversity Intelligence had an effect on the Interest of Accounting Students for a Career as Public Accountants, while the Considerations of the Labor Market and Regulations had no effect on the Interest of Accounting Students for a Career as Public Accountants.Keywords: Work Environment, Social Values, Labor Market Considerations, Regulation, Adversity Intelligence, Career Interest.